The Relationship between Sports Events and Branding; A Symbiosis of Sports and Brand Marketing - Waheed, Javaria; Amin, Salman; Saeed, Robina; Tariq, Muhammad (Pakistan Journal of Humanities and Social Sciences, 2024)
Sports events are witnessed with number of sponsors. The sponsorship of sporting events results in the promotion of a certain brand in exchange. Various sports events attract masses of crowd not only in ground but also on various media. It gives marketers the option to target such large masses of people and turn them into patrons who are devoted to their brand. This study focuses on the relationship between sports event and sponsoring brands. Sponsorship of sports is a great way for a company to become more visible. The brand is exposed to a large audience on athletic stages and in the media by associating with a sporting event or team. Making the most of distribution channels, including press appearances, social media, television broadcasts, and stadium advertising, is crucial to maximizing this visibility. The study is of qualitative nature using in depth interviews. Findings of the study suggest that there exists a mutually beneficial relationship “symbiosis” between sports and sponsoring brands. In the conclusion, this study highlights the dynamic relationship between sports and brand marketing, highlighting the continued significance of sporting events as crucial platforms for consumer interaction and brand promotion in modern international marketplaces.